A thoughtful insight on women entrepreneur's investment attitude - Batool Muhammad Hussain; Umair Baig; Vida Davidaviciene; Ieva Meidute-Kavaliauskiene (Economies, 2021)
This study endeavors to be cognizant of the investment paradigm of women entrepreneurs and reveal their ambitions, professionalism, and desire to form a robust framework in the context of economic development. These persistent attributes of women entrepreneurs for economic development persuaded us to investigate factors that influence women's attitude to make a long-term investment decision in their business regardless of uncertainty. This study adopted a deductive approach and assessed data using the PLS-SEM technique through Smart PLS 3.3.3. Around 330 adequate responses from Karachi and Lahore using a self-designed structured questionnaire revealed that women's investment attitude has a positive significant mediating effect on social, behavioral factors, and investment decisions. Whereas, women's investment attitude did not depict a positive significant mediating effect on personal factors and investment decisions. It was quite interesting to know that uncertainty did not reveal a significant moderating effect between investment attitude and investment decision. The study highlights measures suggested empowering women entrepreneurs who strive to enhance their performance and achieve sustainable development goals without being discouraged by society. Moreover, focusing risk-taking attributes to set an example for those who do not come forth. The novelty of the study in the context of women entrepreneur's investment attitude well contributes to the existing literature and recommends future scholars to expand the horizon of the existing area of the study in the context of cultural, demographic, and seasonal factors, which are also affecting women entrepreneur's investment decisions.
Keywords: 330; women investment decisions; behavioral factors; personal factors; social factors; uncertainty